EU foreign policy perspectives: A call for the revival of the Weimar Triangle - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2008)
The rejection of the Treaty of Lisbon by the Irish has given rise to the possibility of revisiting its central tenets. This is urgently needed for the formulation of a coherent European Foreign and Security Policy. While the new member states tend to have a transatlantic orientation, many old member states are seeking to make Europe more independent from the US. Tension exists between Central and Eastern European security interests and Western European energy policy as regards relations with Russia. The European Neighbourhood Policy is seeing a juxtaposition of unconnected political projects, such as the Mediterranean Union initiated by Paris, and enlargement to in-clude additional Eastern European states, which has the support of many Central and Eastern European nations. The Treaty of Lisbon offers no real solutions to any of this. It does not provide for decisions to be made on the Common Foreign and Security Policy (CFSP) by qualified majority as a rule. Attaining a unanimous decision in the Council on delicate issues of foreign and security policy has become more difficult, especially since the EU's enlargement to 27 member states. Against this background, it seems necessary to encourage the formation of foreign policy groupings, and especially to revitalize the close coordination between Germany, Poland and France in what is known as the "Weimar Triangle"
Keywords: 320